Pengaruh Event Pro Audio Visual, LED, Lighting & Musik Indonesia 2024 Terhadap Citra Perusahaan Kristamedia Pratama: Survei pada Pengunjung Event Pro Audio Visual, Lighting & Musik Indonesia 2024 - Muhammad Kindi Fadhil; Sadiyah El Adawiyah (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
The development of the Mice Industry in Indonesia is growing, this can be seen in 2023 as many as 97.86% of event organizers have returned to being held. The purpose of this study is to measure and analyze the PRO Audio Visual, LED, Lighting & Music Indonesia 2024 Event, the image of PT. Kristamedia Pratama at the PRO Audio Visual, LED, Lighting & Music Indonesia 2024 event, the influence of the PRO Audio Visual, LED, Lighting & Music Indonesia 2024 event on the image of PT Kristamedia Pratama. The theory used for the event is a means for the company as a public relations to introduce and communicate the brand to potential consumers involved in the event and the company's image is a form of intangible asset in a company that has a uniqueness that is easy to identify but difficult to imitate. The research approach uses quantitative. The research method uses a survey. The data collection technique uses simple random sampling with a research sample of 100 respondents. The data collection method uses a questionnaire. The data analysis methods used are validity testing, reliability testing, frequency analysis, correlation analysis, simple linear regression analysis. The results of the study show that events have an overall average value of 4.03, while corporate image has an overall average value of 4.09. Events have a positive and significant effect on corporate image. The r-square value in the coefficient of determination test shows that events have a 45.4% effect on corporate image.